Pengaruh Profitabilitas dan Likuiditas Terhadap Opini Audit Going Concern pada Perusahaan Manufaktur Sub Sektor Proprty dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2016-2021 - Annisa Annisa; Edo Putra (Akuntansi, 2023)
Going concern audit opinion is an opinion issued by the company regarding the feasibility of the company's financial statements to see the future. This study aims to examine the profitability and liquidity of going concern audit opinions in manufacturing companies in the Property and Real Estate sub-sector which are listed on the IDX. This study uses a sample of manufacturing companies in the Property and Real Estate sub-sector which are listed on the IDX in 2016-2021. Based on porposive sampling, the number of manufacturing companies in the Property and Real Estate sub-sector used in this study were 47 companies. Hypothesis testing uses logistic regression using the Spss 23 program.